2017
DOI: 10.3389/fpsyg.2017.00071
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mental Workload in Online Shopping: Are Augmented and Virtual Reality Consistent?

Abstract: A market research company (Nielsen) reported that consumers in the Asia-Pacific region have become the most active group in online shopping. Focusing on augmented reality (AR), which is one of three major techniques used to change the method of shopping in the future, this study used a mixed design to discuss the influences of the method of online shopping, user gender, cognitive style, product value, and sensory channel on mental workload in virtual reality (VR) and AR situations. The results showed that male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…Thus, it seems that the strongest driver of analogical reasoning performance is not necessarily the ability to disengage from attractive semantic or perceptual lure items, but rather focusing on the appropriate relations from the start. In support of this theory, recent work has shown that encouraging children to focus on the A and B items by displaying these items prior to displaying the other items can improve their analogical reasoning performance (Glady, French, & Thibaut, 2017). However, a more general question is, what are the cognitive skills that lead some children to spontaneously adopt this type of strategy?…”
Section: Discussionmentioning
confidence: 96%
“…Thus, it seems that the strongest driver of analogical reasoning performance is not necessarily the ability to disengage from attractive semantic or perceptual lure items, but rather focusing on the appropriate relations from the start. In support of this theory, recent work has shown that encouraging children to focus on the A and B items by displaying these items prior to displaying the other items can improve their analogical reasoning performance (Glady, French, & Thibaut, 2017). However, a more general question is, what are the cognitive skills that lead some children to spontaneously adopt this type of strategy?…”
Section: Discussionmentioning
confidence: 96%
“…The majority of research investigations dissecting the genetics of tinnitus have taken the form of association studies that have revealed few borderline-significant results (Table 2 ). Recently, a genome-wide association study (GWAS) has identified potential metabolic pathways meriting further investigation (Gilles et al, 2017 ) and two twin-study cohorts have uncovered heritability estimates that provide pioneering insight into moderate genetic influences for tinnitus (Bogo et al, 2016 ; Maas et al, 2017 ). Although an excellent review discussing the genetics of tinnitus that touches upon phenotyping strategies and proposed pathophysiological mechanisms has been recently published (Lopez-Escamez et al, 2016 ), the present review exclusively emphasizes the genetic studies that have been published to date, discusses emerging data that suggests a complex or multifactorial genetic etiology, and presents an outlook for future research.…”
Section: Introductionmentioning
confidence: 99%
“…Augmented, virtual and mixed reality are becoming in demand as the technology progresses and augmented reality has been researched academically with regards to consumer engagement (Huang & Huang 2017). In Virtual Reality (VR) and traditional online shopping, males are more focused on practical characteristics with rational thinking whereas females are more focused on the entertainment and emotional catharsis (Zhao et al, 2017).…”
Section: Virtual Shopping Environmentsmentioning
confidence: 99%
“…Neuro-imaging studies using fMRI scans reveals in real life humans who create versions of themselves in AR or use virtually created clothes on themselves feel as though that is their real body in AR otherwise known as a sense of body ownership (Kelley et al, 2002, Kircher et al, 2000, Turk et al 1991. Thus, the concept of embodied cognition to which a sense of 'real to virtual self' is created of AR online shopping is through the body's online experience and self (Zhao et al, 2017).In fact, self related interactive information is a trigger for the brain area responsible for the perception of self (Bargh 1982, Huang & Huang 2017.…”
Section: Virtual Shopping Environmentsmentioning
confidence: 99%
See 1 more Smart Citation